Species perceived to be dangerous are more likely to have distinctive local names - Harith Farooq; Cláudio Bero; Yolanda Guilengue; Clementina Elias; Yasalde Massingue; Ivo Mucopote; Cristóvão Nanvonamuquitxo; Johan Marais; Alexandre Antonelli; Søren Faurby (BMC, 2021)
Abstract Background Species with direct uses, such as sources of food, shelter, building material and medicine tend to have more specific local names. But could the same apply for species that people fear? Methods To address this question, here we explore the behavior and perception of species diversity and dangerousness through a survey of 1037 households in nine villages in Cabo Delgado, northern Mozambique. We compare people's knowledge of snakes with that of lizards and amphibians. Results We find that northern Mozambicans know four to five times more local names for snakes than for lizards and frogs, despite the local species richness of snakes being comparable to the diversity of lizards and frogs. We further find that local knowledge was on par with the academic literature regarding snakebite symptoms. Conclusions Our results suggest that fear can increase the level of specificity in naming species among indigenous communities, which could lead to biases in the mapping and protection of species that include data from citizen reports.